Effect of Holothuria leucospilota extracted saponin on maturation of mice oocyte and granulosa cells - Fereshteh Delghandi Moghadam; Javad Baharara; Saeedeh Zafar Balanezhad; Mohsen Jalali; Elaheh Amini (Wolters Kluwer Medknow Publications, 2016)
Sea cucumbers saponins are triterpenoid glycosides which exert beneficial biomedical effects. This study was performed to assess the effect of saponin extracted from sea cucumber Holothuria leucospilota (H. leucospilota) on maturation of mice oocytes and granulosa cells. The germinal vesicles oocytes were collected from 6-8 weeks old Naval Medical Research Institute (NMRI) mice ovaries, randomly divided into untreated and four experimental groups and cultured In vitro. Maturation medium was supplemented with 0, 1, 2, 4 and 8 μg/ml saponin for 12 days. The rates of maturation were recorded through morphological observation by measurement of follicle diameter during treatment. After 4 days, the effects of saponin on granulosa cells were investigated by reactive oxygen species (ROS) measurement, super oxide dismutase (SOD) activity, caspase assay and tumor necrosis factor-alpha (TNF-α) expression. The oocyte maturation rate was significantly higher in treated groups (1 μg/ml). The ROS and SOD assays demonstrated the antioxidant potential of saponin. The caspase assay exhibited that optimum concentrations of saponin (1, 2 μg/ml) reduced caspase activity in granulosa cells. Flow cytometry showed that optimum concentration of saponin promoted oocyte maturation via down regulation of TNF-α as follicular degenerative factor in nursing cells. These results proposed that maturation rate were obtained after the incorporation of 1 μg/ml sea cucumber saponin. Moreover, the extracted saponin at concentrations of 1, 2 μg/ml enhanced follicle growth which is accompanied by attenuating ROS formation, elevating SOD activity and reducing TNF-α expression in granulosa cells. But, further examinations are required to understand precise mechanisms of saponin action on oocyte and granulosa cells.